A "Pouch Test" for Characterizing Gas Permeability of Geomembranes. Issue 4 (1st January 2002) - Barroso, M.; Pierson, P.
Abstract : To characterize the gas permeability of seamed or non-seamed geomembranes, laboratory tests were carried out using a new permeability test: the gas permeability pouch test. Circular and rectangular "pouches" made of two pieces of high density polyethylene (HDPE) geomembrane were tested. To study the permeability of the geomembrane itself, the pouch was made of two circular geomembrane sheets welded together (the percentage of the seamed area is negligible compared to the non-seamed area). To study the permeability of the HDPE seams, two rectangular pieces of geomembrane were welded together using the thermal-hot dual wedge method (where the percentage of the seamed area is predominant). For this test, specimens are pressurized with a gas (e.g., nitrogen, in this case), and immersed either in air or in water. The flow of gas is indicated by a decrease in the pressure inside the pouch. The test results obtained are in agreement with results reported in the literature and show that the gas permeability pouch test can be used to characterize geomembrane permeability, with the advantages of being easy to carry out and allowing the assessment of the seam quality by quantitative measurement of their permeance.